I Could Enjoy Teaching: The Case of Physics - Hillier, J; de Winter, J; Twidle, J (2013)
There is a chronic international shortage of mathematics and science teachers, particularly physicists. The study reported here examines why physicists become teachers and why they stay in teaching. Physicists from seven preservice teacher training cohorts from three English universities were invited to answer an online survey with follow-up telephone interviews exploring their decisions to become teachers and the factors influencing their retention in the profession. Key to becoming teachers were pivotal experiences revealing teaching as a career they could enjoy. Analysis also showed a frequent lack of support and feelings of isolation for beginning physics teachers in schools. © 2013 Copyright Taylor and Francis Group, LLC.